2008
DOI: 10.1186/cc6897
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve sonography in the diagnostic evaluation of adult brain injury

Abstract: Introduction The optic nerve sheath diameter (ONSD) may be increased in brain-injured patients, especially children, with intracranial hypertension. We investigated whether measurements of ONSD correlated with simultaneous noninvasive and invasive measurements of the intracranial pressure (ICP) in brain-injured adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
219
2
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(252 citation statements)
references
References 38 publications
(65 reference statements)
15
219
2
16
Order By: Relevance
“…As a result intracranial pressure changes are transmitted through the subarachnoid space to the optic nerve [63]. Several studies have shown that ONSD correlates with the intracranial blood pressure measurements [64,65] and the technique has now been standardized [66]. The patient is studied in the supine position; a layer of gel is applied over the closed eyelid and a high-frequency linear probe is gently positioned on the temporal area of the eyelid to visualize the entry of the optic nerve into the globe.…”
Section: Post-traumatic Intracranial Lesion the Optic Nervementioning
confidence: 99%
“…As a result intracranial pressure changes are transmitted through the subarachnoid space to the optic nerve [63]. Several studies have shown that ONSD correlates with the intracranial blood pressure measurements [64,65] and the technique has now been standardized [66]. The patient is studied in the supine position; a layer of gel is applied over the closed eyelid and a high-frequency linear probe is gently positioned on the temporal area of the eyelid to visualize the entry of the optic nerve into the globe.…”
Section: Post-traumatic Intracranial Lesion the Optic Nervementioning
confidence: 99%
“…Enzymes and free radicals in the cells fragmented as a result of necrosis are released and enter a vicious cycle that causes more neuron destruction. Changes in the cerebral blood flow developing as a result of CVD, the breakdown of cerebral perfusion pressure due to edema that develops at the tissue level, and ineffective CSF circulation cause an increase in ICP (17,22,23). The ON is unique because it represents an extension of the central nervous system and has a cover (dura, arachnoid, and pia) (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it must be remembered that papillary edema, which is caused by ICP, may lead to increased ONSD (26,27). In some studies, ONSD has been reported as 4.9-5.9 mm in cases of ICP (17,20,30,31). Soldatos et al (17) determined ONSD as 6.1 mm in patients with severe brain injuries, 4.2 mm in moderate-severe injuries, and 3.6 mm in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive ICP Monitoring A variety of methods to measure ICP noninvasively have been studied, including transcranial Doppler ultrasonography [17,18], optic nerve sheath diameter [19][20][21], fundoscopic papillary examination [22], and tympanic membrane displacement [23]. Unfortunately, all of these techniques are subject to artifact, have been studied in relatively small numbers of patients, require significant expertise to perform, and have only limited correlation with invasively obtained ICPs.…”
Section: Invasive Icp Monitoringmentioning
confidence: 99%